2018
DOI: 10.1186/s12906-018-2277-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of Angelica gigas by increasing immune response and stimulating natural killer and natural killer T cells

Abstract: BackgroundThe polysaccharide component of Angelica gigas induces immuno-stimulatory effects on innate immune cells. However, it is unclear whether A. gigas’ adjuvant activity on the immune system can elicit anti-cancer responses.MethodsA water-soluble immuno-stimulatory component of A. gigas was prepared. How this ISAg modulated the activation of innate immune cells such as dendritic cells (DCs) was examined. ISAg-induced cytotoxic activity via natural killer (NK) and NKT cells was also tested using a tumor-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…Angelica gigas Nakai (AGN) belongs to the Umbelliferae family and has been traditionally used in oriental remedies due to its many advantageous attributes, such as antiepileptic, hepatoprotective, anti-cancer, anti-inflammatory, and anti-amnesic activities [12][13][14][15][16][17]. Concerning the case of hair growth using AGN, the extract of the roots of AGN is frequently included as a hair growth-facilitating component in combined herbal extracts [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Angelica gigas Nakai (AGN) belongs to the Umbelliferae family and has been traditionally used in oriental remedies due to its many advantageous attributes, such as antiepileptic, hepatoprotective, anti-cancer, anti-inflammatory, and anti-amnesic activities [12][13][14][15][16][17]. Concerning the case of hair growth using AGN, the extract of the roots of AGN is frequently included as a hair growth-facilitating component in combined herbal extracts [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that the water-soluble polysaccharide fraction of A. gigas , ISAg, elicits anticancer effects through cytotoxic activity of NK and NKT cells (Kim et al. 2018b). Since it is well established that the overproduction of IL12p40 by DCs leads to Th1 polarization of conventional CD4 + and CD8 + T cells (Mayordomo et al.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that ISAg-mediated IL12 production by DCs and macrophages is dependent on the TLR4 pathway (Kim et al. 2018b). However, since it was reported that TLR2 and TLR4 ligands directly activate NK and NKT cells (Martinez et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations